Hubungan antara Toleransi pada Stress dengan Kecenderungan Mengkonsumsi Minuman Alkohol secara Berlebih-lebihan - Azah Rawan Sangun dan Bimono (LPPM Universitas Proklamasi 45, 2010)
One hundred subjects aged 17-19 years old participated in this study. This study concerned about young generation’s habit on consuming alcohol excessively. They were guests in a caft. Objective of this study is explaining the influence of stress tolerance on the excessively alcohol consumption behavior. The item validation analysis for the Stress Tolerance Scale found that the r„ was ranged .206.756, whilst the ru for the Behavior Tendency on Consuming Alcohol Excessively Scale was ranged .215-.631. The hypothesis analysis using the product moment correlation revealed that the stress tolerance indeed influenced the behavior tendency on consuming alcohol excessively (r ^ ■ -.215, p«.05). Contribution of the independent variable toward the dependent variable was low (4.6%) albeit significant. Several research weakness and recommendations for future research were discussed.